T-cell cytokine profiles are altered in childhood asthma exacerbation. - Calderon, Czarina; Rivera, Luis; Hutchinson, Paul; Dagher, Hayat; Villanueva, Elmer; Ghildyal, Reena; Bardin, Philip G; Freezer, Nicholas J (Respirology (Carlton, Vic.), 2009)
Stable asthma is characterized by the production of Th2 cytokines, although Th1 cytokines may play a key role in aspects such as airway hyper-responsiveness. This study explored cytokine profiles associated with asthma exacerbation.
Keywords: Asthma; Case-Control Studies; CD4-CD8 Ratio; Child; Child, Preschool; Female; Flow Cytometry; Glucocorticoids; Humans; Immunoglobulin E; Interferon-gamma; Interleukin-13; Interleukin-4; Male; Prednisolone; T-Lymphocytes; Th1 Cells; Th2 Cells